Organizational Goal Vagueness and Its Impact on Employee Motivation - Hasyim Hasyim; Muhammad Bakri (STIE Amkop Makassar, 2024)
This study aims to explore the impact of organizational goal vagueness (OGV) on employee motivation, focusing on intrinsic and extrinsic factors. The research investigates how unclear goals influence employee productivity, engagement, and well-being within organizations. The study employs a systematic literature review (SLR) approach, analyzing recent studies and theories to synthesize findings on the effects of goal ambiguity. The study examines various empirical and theoretical contributions to the topic by reviewing peer-reviewed articles. The findings reveal that goal ambiguity significantly reduces employee motivation by creating confusion and uncertainty about roles and expectations. Both intrinsic motivation (personal satisfaction) and extrinsic motivation (rewards and recognition) are negatively impacted. The research also highlights that goal vagueness undermines employee engagement and increases stress, leading to burnout and decreased productivity. Additionally, clear and well-communicated goals are essential for enhancing motivation, improving performance, and fostering organizational success. The study suggests that organizations must prioritize clear goal-setting and transparent communication to mitigate the adverse effects of goal vagueness. Regular feedback, aligned objectives, and better leadership communication are essential to improve employee motivation and ensure organizational effectiveness. These findings provide practical recommendations for managers aiming to foster a motivated and engaged workforce.